Impact of landfill density on transport and hydraulic characteristics of recirculated leachate - Jiang, Guobin (Environmental technology, 2019)
To achieve a uniform water distribution and to promote the stabilization of bioreactor landfills, the effects of different density on the transport and hydraulic characteristics of recirculated leachate were studied in a Li+ tracer experiment. The landfill density was related negatively to the maximum production rate of leachate, the percentage of Li+ tracer solution and the cumulative amount of Li+ that washed out in the first recirculation round. The cumulative amount of Li+ that was washed out accounted for 92.61%, 82.07% and 75.25% of the injection volume in three waste columns (1#, 2# and 3#) with landfill densities of 497.5, 726.4 and 970.1 kg m-3 at the thirtieth recirculation, respectively. The results revealed that a greater landfill density yielded a smaller amount of Li+ that was washed out per recirculation cycle and the cumulative amount of Li+ washed out, and a longer contact time between the waste and leachate. Moreover, waste columns 1#, 2# and 3# are reactors with a high dispersion and obvious retention zones, and their Morrill Dispersion Index (MDI) values were 25.00, 34.51 and 24.55, respectively. A short-flow phenomenon is obvious in the reactor with a low landfill density. Furthermore, the plug-flow effect is relatively better in the reactor with a high landfill density. To achieve a uniform distribution of recirculated leachate in the landfill, the MDI of the reactor should be reduced combined with other measures, such as pre-crushing and different recirculation schemes